Graduate Unemployment Problem and the Nigeria University System: 1970-85. - Oladeji, Sunday Idowu (Obafemi Awolowo University, 2014)
This study has attempted to understand the nature and causes of graduate unemployment in Nigeria. The relevance of the 'over-production hypothesis' was addressed. A framework for the validation of the hypothesis was developed and applied to the Nigerian situation in the period 1970 - 85. The analytical technique made use of the Incremental Labour-Output Ratio (ILOR) technique to determine the manpower need of each of the three plan periods spanned by the study-period.